Metronomic chemotherapy with daily low-dose temozolomide and celecoxib in elderly patients with newly diagnosed glioblastoma multiforme: a retrospective analysis - Welzel, Grit; Brehmer, Stefanie; Deimling, Andreas von; Seiz-Rosenhagen, Marcel; Schmiedek, Peter; Wenz, Frederik; Giordano, Frank Anton (Journal of neuro-oncology, 2015)
Chemotherapy is often omitted in elderly patients with glioblastoma multiforme due to a fear of side effects. We applied metronomic chemotherapy with low-dose temozolomide and celecoxib (LD-TEM/CEL) during and after external beam radiotherapy (EBRT) and here report on how this regimen compares to standard temozolomide radiochemotherapy (SD-TEM) in elderly patients. We retrospectively analyzed records of 146 patients aged 65 years and older that underwent EBRT. Factors of interest were age, performance status, comorbidities, MGMT status, therapy (resection/biopsy, radiotherapy/dose, chemotherapy/regimen/dose), progression-free (PFS) and overall survival (OS) status. Irrespective of the regimen, addition of chemotherapy more than doubled median survival rates (EBRT only: 4.2 months; EBRT + LD-TEM/CEL: 8.5 months; EBRT + SD-TEM: 10.8 months; p ≤ 0.008). Although patients receiving metronomic LD-TEM/CEL were significantly older (62 % were ≥75 years vs. 22 %; p < 0.001), had significantly lower performance scores (50 % had a KPS <70 vs. 28 %; p = 0.049) and were significantly more comorbid (73 % had ≥4 comorbidities vs. 37 %; p = 0.002) than patients of the SD-TEM group, there were no significant differences in PFS and OS. Independent of other factors, omission of chemotherapy significantly impairs progression-free and overall survival. With all the limitations of a retrospective analysis, our data suggest that metronomic chemotherapy with LD-TEM/CEL may be equieffective and eventually better tolerated than SD-TEM. It may be offered to elderly patients that are not eligible for standard chemotherapy.